Acrylic Bone Cement Incorporated with Low Chitosan Loadings (2020)
Despite the potential of acrylic bone cement (ABC) loaded with chitosan (CS) for orthopedic applications, there are only a few in vitro studies of this composite with CS loading ≤ 15 wt.% evaluated in bioactivity tests in simulated body fluid (SBF) for duration > 30 days. The purpose of the present work was to address this shortcoming of the literature. In addition to bioactivity, a wide range of cement properties were determined for composites with CS loading ranging from 0 to 20 wt.%. These properties included maximum exotherm temperature (Tmax), setting time (tset), water contact angle, residual monomer content, flexural strength, bending modulus, glass transition temperature, and water uptake. For cement with CS loading ≥ 15 wt.%, there was an increase in bioactivity, increase in biocompatibility, decrease in Tmax, increase in tset, all of which are desirable trends, but increase in residual monomer content and decrease in each of the mechanical properties, with each of these trends, were undesirable. Thus, a composite with CS loading of 15 wt.% should be further characterized to explore its suitability for use in low-weight-bearing applications, such as bone void filler and balloon kyphoplasty